2019
DOI: 10.1167/iovs.19-27331
|View full text |Cite
|
Sign up to set email alerts
|

Size and Shape of Bruch's Membrane Opening in Relationship to Axial Length, Gamma Zone, and Macular Bruch's Membrane Defects

Abstract: PURPOSE. To assess axial elongation-associated characteristics in Bruch's membrane opening (BMO) as the inner optic nerve head lamella. METHODS. Participants of the population-based Beijing Eye Study without glaucoma underwent optical coherence tomography for measurement of the BMO size and shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 40 publications
6
70
1
Order By: Relevance
“…However, this relationship seems to be non-linear in clinical practice, and Jonas et al 1 described the prevalence and size of PPA −BM increased steeply, starting at an axial length of 26.5 mm, in their histomorphometric investigations of human globes. Recently, Zhang et al 20,21 demonstrated a steep increase in BMO diameters beyond an axial length of 26.0 mm and reported that such BMO enlargement was significantly associated with the large PPA −BM in myopic eyes. Similarly, we found a significant positive association between the PPA −BM width and BMO area, after adjusting for significant confounders.…”
Section: Discussionmentioning
confidence: 99%
“…However, this relationship seems to be non-linear in clinical practice, and Jonas et al 1 described the prevalence and size of PPA −BM increased steeply, starting at an axial length of 26.5 mm, in their histomorphometric investigations of human globes. Recently, Zhang et al 20,21 demonstrated a steep increase in BMO diameters beyond an axial length of 26.0 mm and reported that such BMO enlargement was significantly associated with the large PPA −BM in myopic eyes. Similarly, we found a significant positive association between the PPA −BM width and BMO area, after adjusting for significant confounders.…”
Section: Discussionmentioning
confidence: 99%
“…The optic nerve head can be regarded as a three-layered hole in the coats of the globe, with BM opening forming the inner layer, the choroidal opening the middle layer, and the scleral opening covered by the lamina cribrosa forming the outer layer. A recent optical coherence tomographical study showed that in medium myopic eyes the three layers often are not aligned to each other but that medium myopic eyes often show an overhanging of BM into the intrapapillary region on the nasal side of the optic disc 13 . Correspondingly, there is a lack of BM at the temporal optic disc side what is the equivalent of parapapillary gamma zone (as defined by the absence of BM).…”
Section: Discussionmentioning
confidence: 99%
“…We did not take into account potential differences in the anatomy and biomechanical properties of the various layers of the LC, nor did we consider lateral movements of the LC in dependence of changes of the examined parameters and in dependence of the obliqueness of the optic nerve canal and the spatial relationship between Bruch’s membrane opening and the lamina cribrosa position. 66, 67…”
Section: Discussionmentioning
confidence: 99%